Towards Developing a Sustainable Campus: Best Practice Approach - Faizatul Akmar Abdul Nifa; Wan Nurul Mardiah Wan Mohd Rani; Mohd Noorizhar Ismail; Syukran Abdul Rahim (International Journal of Supply Chain Management, 2016)
Campus Sustainability has become challenging because it requires active participation and coordination of related stakeholders particularly the campus community itself. Previous research has pointed out that for a campus to be sustainable, consideration to the three pillars of sustainable development is essential. This refers to the preservation of the environment, continuous economic growth and social sustainability. Good governance and best practice is the key to achieve a sustainable campus. This could be achieved through active coordination and participation between the management, administrative and operational departments, and the academic department and its local community. Continuous support of the efforts to achieve a sustainable campus will be reflected in the quality of the teaching, learning and other related activities. Hence it is important to frame out the best practice that comprises a holistic approach and strategies to achieve a sustainable campus. This paper provides a review on the status of higher education development in Malaysia that also looks into the issues and challenges of achieving a sustainable campus. Subsequently, the authors propose a conceptual framework of best practice to achieve sustainable campus aimed at improving the current campus sustainability plan.